Pertumbuhan Aklimatisasi Bibit Tiga Varietas Krisan pada Beberapa Persentase Naungan - Rizky Hasanan; Agustina Listiawati; Asnawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Chrysanthemum is an ornamental plant widely cultivated in Indonesia, with various varieties that have unique and attractive characteristics. Each variety responds differently to changes in light intensity. Providing shade can help regulate the light intensity received by chrysanthemum seedlings during the acclimatization stage. This study aimed to determine the best shade percentage for the acclimatization growth of three chrysanthemum varieties. The research was conducted in the screenhouse of the Faculty of Agriculture, Tanjungpura University, for three months, from October to December 2024. The experiment used a Split Plot Design (Split Plot) with a Randomized Block Design (RBD), consisting of two factors: shade percentage and variety. There were three levels of shade and three chrysanthemum varieties, resulting in nine treatment combinations. Each treatment was repeated three times, with each replication consisting of three sample plants, resulting in 81 experimental units. The shade percentages used were 25% (n1), 50% (n2), and 75% (n3), and the varieties tested were Xanne (v1), Suciyono (v2), and Pinka Pinky (v3). Observed variables included plant survival rate, plant height, stem diameter, internode length, number of internodes, number of flower primordia, leaf color changes, along with supporting data such as temperature, humidity, and light intensity. The results showed that 50% shade was effective in promoting plant height and the number of flower primordia in the three varieties: Xanne, Suciyono, and Pinka Pinky. The Suciyono variety exhibited good vegetative and generative growth under all shade percentages.